Role of BRCA Mutations in the Modulation of Response to Platinum Therapy - Mylavarapu, Sanghamitra; Das, Asmita; Roy, Monideepa (Frontiers in Oncology, 2018)
Recent years have seen cancer emerge as one of the leading cause of mortality worldwide with breast cancer being the second most common cause of death among women. Individuals harboring BRCA mutations are at a higher risk of developing breast and/or ovarian cancers. This risk is much greater in the presence of germ-line mutations. BRCA1/2 play crucial roles in the DNA damage response and repair pathway, a function that is critical in preserving the integrity of the genome. Mutations that interfere with normal cellular function of BRCA not only lead to onset and progression of cancer but also modulate therapy outcome of treatment with platinum drugs. In this review, we discuss the structural and functional impact of some of the prevalent BRCA mutations in breast and ovarian cancers and their role in platinum therapy response. Understanding the response of platinum drugs in the context of BRCA mutations may contribute towards developing better therapeutics that can improve survival and quality of life of patients.